The Role of Venture Capital in Advancing Digital Health in Germany : A Practitioner’s Perspective on Innovation and Adoption - Zikulnig, Susanne; Andera, Michal, 1984-; Potančok, Martin; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis explores the role of venture capital (VC) in further promoting the development of digital health in Germany by including a survey with practitioners and employees from the healthcare sector, on their perspective. As technologies such as telemedicine, AI-driven diagnostics and other digital health solutions are revolutionizing the healthcare sector, VC funding has been critical to growth. Nevertheless, the alignment of VC investment priorities with those of healthcare professionals in Germany has not been fully explored yet. In this research, a mixed-method approach was employed to explore the impact of VC-driven innovations on healthcare adoption and outcomes. This paper analyses the alignment of VC investment trends and the adoption of digital health tools in Germany, through a literature review about VC trends and a survey of healthcare professionals. The research investigates whether there are critical misalignments between venture capital investment strategies and the practical needs of healthcare professionals, with the goal of enabling a better understanding of the innovation environment in digital health.
Vedoucí práce: Michal Andera
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses